Dicyanobenzothiadiazole (DCBT) Organic Dye as a Visible Light Absorbing Strong Photoinduced Oxidant with a 16 Microsecond Long‐Lived Excited State. Issue 2 (20th November 2022) - Li, Qing Yun; Hunt, Leigh Anna; Wijesinghe, Kalpani Hirunika; Curiac, Christine; Williams, Ashley; Dass, Amala; Hammer, Nathan I.; Delcamp, Jared H.
Abstract: Strong photoinduced oxidants are important to organic synthesis and solar energy conversion, to chemical fuels or electric. For these applications, visible light absorption is important to solar energy conversion and long‐lived excited states are needed to drive catalysis. With respect to these desirable qualities, a series of five 5, 6‐dicyano[2, 1, 3]benzothiadiazole (DCBT) dyes are examined as organic chromophores that can serve as strong photooxidants in catalytic systems. The series utilizes a DCBT core with aryl groups on the periphery with varying electron donation strengths relative to the core. The dyes are studied via both steady‐state and transient absorption and emission studies. Additionally, computational analysis, voltammetry, crystallography, and absorption spectroelectrochemistry are also used to better understand the behavior of these dyes. Ultimately, a strong photooxidant is arrived at with an exceptionally long excited state lifetime for an organic chromophore of 16 µs. The long‐lived excited state photosensitizer is well‐suited for use in catalysis, and visible light driven photosensitized water oxidation is demonstrated using a water‐soluble photosensitizer. Abstract : A strong photooxidant organic dye that absorbs visible light is designed with a long‐lived excited state at 16 microseconds. This dye can power photocatalytic water oxidation and is a more potent photooxidant than acridinium based photosensitizers with an excited state potential of 2.5 V versus normal hydrogen electrode.